Compound based on sulfur-phosphorus heterocyclic ring receptor and nitrogen-containing heterocyclic ring donor as well as synthesis method and application of compound

By designing compounds based on thiophosphate heterocyclic acceptors and nitrogen-containing heterocyclic donors, using the electron-absorbing ability and steric hindrance effect of phosphineoxy groups, the shortcomings of TADF luminescent materials in terms of luminescence efficiency and stability are solved, and the results are achieved. Efficient blue light TADF luminescence performance and improved stability of electroluminescent devices.

CN119431455AActive Publication Date: 2025-02-14HEILONGJIANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411454481.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-13
Filing Date
2022-09-23
Publication Date
2025-02-14
Estimated Expiration
2042-09-23

Smart Images

  • Figure BDA0005090073590000021
    Figure BDA0005090073590000021
  • Figure BDA0005090073590000041
    Figure BDA0005090073590000041
  • Figure BDA0005090073590000051
    Figure BDA0005090073590000051
Patent Text Reader

Abstract

The invention provides a compound based on a sulfur-phosphorus heterocyclic ring receptor and a nitrogen-containing heterocyclic ring donor, and in the compound, the sulfur-phosphorus heterocyclic ring receptor is used as a parent and has a nitrogen-containing heterocyclic ring substituent group. The compound has thermal excitation delayed fluorescence luminescence performance, the ICT effect of a system is optimized by utilizing the moderate electron withdrawing capability of phosphine oxide groups in molecules, the RISC efficiency is improved, and meanwhile, exciton quenching caused by excited state structure relaxation and intermolecular interaction is inhibited by utilizing the steric effect of the phosphine oxide groups, so that the luminescence efficiency is improved. Therefore, the photoluminescence quantum yield, the luminescence efficiency and the device stability of the blue light TADF luminescent material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of application (2022111668919). The application date of the original application is (September 23, 2022), the application number is (2022111668919) and the invention name is based on sulfur-phosphorus heterocyclic acceptor and nitrogen-containing heterocyclic donor compounds, their synthesis methods and applications. Technical Field

[0002] The invention belongs to the technical field of organic electroluminescent materials, and in particular relates to a compound based on a sulfur-phosphorus heterocyclic acceptor and a nitrogen-containing heterocyclic donor, a synthesis method and an application thereof. Background Art

[0003] High-efficiency, low-voltage driven organic electroluminescence has brought revolutionary innovation to the development of light-emitting diodes. The research on organic light-emitting materials and devices has attracted widespread attention and in-depth research. Since the first OLED device, OLED technology has developed from the first-generation fluorescence (Fluorescence, FL) technology, the second-generation phosphorescence (Phosphorescence, PH) technology to the third-generation thermally activated delayed fluorescence (Tadf) technology. Phosphorescence technology uses phosphorescent dyes to achieve electroluminescence. These dyes are generally heavy precious metal complexes, and the heavy metals involved are not only expensive and unsustainable, but also pollute the environment. In contrast, the third-generation Tadf technology is mainly based on pure organic molecules with a push-pull electronic architecture. Through the reverse intersystem crossing (RISC) process from the triplet energy level (T1) of the molecule to the singlet energy level (S1), the non-luminescent triplet excitons are converted into radiative singlet excitons, thus achieving a theoretical internal quantum efficiency of 100%. It can be seen that TADF technology not only retains the low cost, environmental friendliness and sustainability of fluorescent materials, but also has the high efficiency of phosphorescent technology. Since the Adachi research group reported the first high-efficiency TADF device in 2012, related research has rapidly developed into one of the hot spots in the field of organic optoelectronic materials and devices. In less than 10 years, the performance of monochrome TADF devices has approached that of phosphorescent devices, showing excellent development and application potential.

[0004] At present, high-efficiency and high-color-purity thermally excited delayed fluorescence TADF luminescent materials are still one of the key bottlenecks that restrict the real application of TADF technology. TADF materials must reduce the singlet-triplet splitting (ΔE) through sufficiently strong intramolecular charge transfer (ICT) ST ) to promote TADF emission. The commonly used method is to reduce the electron donating ability of the donor (Donor, D) or to enhance the frontier orbital separation and RISC by controlling the configuration, but at the expense of reducing the luminescence efficiency.

[0005] Therefore, how to design and prepare high-efficiency, high-color-purity thermally excited delayed fluorescence TADF luminescent materials with high luminescence efficiency is still one of the problems that need to be further studied and solved in TADF luminescent materials. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a class of compounds with sulfur-phosphorus heterocycle as the parent and nitrogen-containing heterocyclic substituents, which have thermally excited delayed fluorescence luminescence performance, good luminescence purity and high luminescence efficiency. The phosphine oxygen group's moderate electron-withdrawing ability is used to optimize the ICT effect of the system, improve the RISC efficiency, and at the same time, the steric effect of the phosphine oxygen group is used to inhibit the relaxation of the excited state structure and the exciton quenching caused by intermolecular interactions, thereby improving the photoluminescence quantum yield (PLQY) of the blue light TADF luminescent material, and improving the device luminescence efficiency and device stability.

[0007] The first aspect of the present invention aims to provide a compound based on a sulfur-phosphorus heterocyclic acceptor and a nitrogen-containing heterocyclic donor, wherein the sulfur-phosphorus heterocyclic acceptor serves as a parent and carries a nitrogen-containing heterocyclic substitution group.

[0008] The sulfur-phosphorus heterocyclic receptor and nitrogen-containing heterocyclic donor compound have the following structure:

[0009]

[0010] Wherein, R1 and R2 are selected from nitrogen-containing heterocyclic substituents or hydrogen, and the nitrogen-containing heterocyclic substituents are selected from 9,9-dimethylacridin-N-yl, 9,9-diphenylacridin-N-yl, N-phenothiazinyl or N-phenoxazinyl; R2 is selected from nitrogen-containing heterocyclic substituents, preferably selected from N-dimethylacridinyl, N-diphenylacridinyl, N-phenothiazinyl or N-phenoxazinyl.

[0011] The second aspect of the present invention aims to provide a preparation method based on a sulfur-phosphorus heterocyclic acceptor and a nitrogen-containing heterocyclic donor compound, wherein the method is prepared by a carbon-nitrogen coupling reaction of a halogenated sulfur-phosphorus heterocyclic compound and a nitrogen-containing heterocyclic compound in the presence of a palladium catalyst under an alkaline environment.

[0012] The method comprises the following steps:

[0013] Step 1, preparing a halogenated sulfur-phosphorus heterocyclic compound;

[0014] Step 2, adding a halogenated sulfur-phosphorus heterocyclic compound, a nitrogen-containing heterocyclic donor compound, a palladium catalyst and an alkaline substance into a reaction solvent, stirring for reaction, and obtaining a reaction solution;

[0015] Step 3: post-treating the reaction solution to obtain a sulfur-phosphorus heterocyclic receptor and a nitrogen-containing heterocyclic donor compound.

[0016] The third aspect of the present invention aims to provide the use of the sulfur-phosphorus heterocyclic acceptor and the nitrogen-containing heterocyclic donor compound as a light-emitting layer material for preparing an electroluminescent device.

[0017] The fourth aspect of the present invention aims to provide an electroluminescent device, wherein the light-emitting layer material of the electroluminescent device comprises the sulfur-phosphorus heterocyclic acceptor and the nitrogen-containing heterocyclic donor compound.

[0018] The sulfur-phosphorus heterocyclic acceptor and nitrogen-containing heterocyclic donor compound provided by the present invention has the following beneficial effects:

[0019] (1) The present invention is based on a binary DA system composed of a sulfone acceptor and a donor, and optimizes the ICT effect of the system by utilizing the moderate electron-withdrawing ability of the phosphine group without changing or slightly changing the luminescent color, thereby improving the RISC efficiency. At the same time, the steric effect of the phosphine group is utilized to inhibit the relaxation of the excited state structure and the exciton quenching caused by intermolecular interactions, thereby improving the PLQY of the blue light TADF luminescent material and improving the device efficiency and device stability.

[0020] (2) The target compound can be prepared in a controllable manner based on the sulfur-phosphorus heterocyclic receptor and the nitrogen-containing heterocyclic donor compound through reasonable molecular structure design and synthetic route design.

[0021] (3) The pyrolysis temperature of compound (I) and compound (II) in the present invention can reach above 360°C. At the luminescence peak of about 505nm, the current efficiency reaches a maximum value of up to 64.5cd·A -1 , the power efficiency reaches the maximum value up to 75.1lm·W -1 , achieving a maximum external quantum efficiency of 26.5%.

[0022] (4) The pyrolysis temperature of compound (III) and compound (IV) in the present invention can reach above 410°C. At the luminescence peak of about 505nm, the current efficiency reaches a maximum value of up to 89.9cd·A -1 , the power efficiency reaches the maximum value up to 108.6lm·W -1 , and the maximum external quantum efficiency reached 27.2%.

[0023] (5) The pyrolysis temperature of compound (V) and compound (VI) in the present invention can reach above 470°C. At the luminescence peak position of 493-498, the current efficiency reaches a maximum value of up to 65.9 cd·A -1 , the power efficiency reaches the maximum value up to 78.1lm·W -1 , and the maximum external quantum efficiency reached 22.7%.

[0024] (6) The pyrolysis temperature of compound (VII) and compound (VIII) in the present invention can reach above 360°C. At the luminescence peak of 495-505nm, the current efficiency reaches a maximum value of up to 66.9 cd·A -1 , the power efficiency reaches the maximum value up to 82.4lm·W -1 , and the maximum external quantum efficiency reached 22.1%. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The ultraviolet, fluorescence and phosphorescence spectra of the compound (I) of the present invention are shown; Figure 2 The voltage-current density relationship curve of the device 1 of the present invention is shown; Figure 3 The ultraviolet, fluorescence and phosphorescence spectra of the compound (II) of the present invention are shown; Figure 4 The voltage-current density relationship curve of the device 2 of the present invention is shown; Figure 5 The ultraviolet, fluorescence and phosphorescence spectra of the compound (III) of the present invention are shown; Figure 6 The voltage-current density relationship curve of the device 3 of the present invention is shown; Figure 7 The ultraviolet, fluorescence and phosphorescence spectra of the compound (IV) of the present invention are shown; Figure 8 The voltage-current density relationship curve of the device 4 of the present invention is shown; Fig. 9 The ultraviolet, fluorescence and phosphorescence spectra of the compound (V) of the present invention are shown; Fig.10 The voltage-current density relationship curve of the device 5 of the present invention is shown; Fig.11 The ultraviolet, fluorescence and phosphorescence spectra of the compound (VI) of the present invention are shown; Fig.12 The voltage-current density relationship curve of the device 6 of the present invention is shown; Fig.13 The ultraviolet, fluorescence and phosphorescence spectra of the compound (VII) of the present invention are shown; Fig.14The voltage-current density relationship curve of the device 7 of the present invention is shown; Fig.15 The ultraviolet, fluorescence and phosphorescence spectra of the compound (VIII) of the present invention are shown; Fig.16 The voltage-current density relationship curve of the device 8 of the present invention is shown. DETAILED DESCRIPTION

[0026] The present invention is described in detail below through specific implementation modes, and the characteristics and advantages of the present invention will become clearer and more specific with these descriptions.

[0027] The present invention provides a compound based on a sulfur-phosphorus heterocyclic acceptor and a nitrogen-containing heterocyclic donor, wherein the sulfur-phosphorus heterocyclic acceptor and the nitrogen-containing heterocyclic donor in the molecule have a strong ICT, thereby improving the RISC efficiency, suppressing exciton quenching by utilizing the molecular structure, and improving the photoluminescence quantum yield of the compound as a TADF luminescent material, thereby achieving improved performance of an electroluminescent device.

[0028] The first aspect of the present invention provides a compound based on a sulfur-phosphorus heterocyclic acceptor and a nitrogen-containing heterocyclic donor, wherein the sulfur-phosphorus heterocyclic acceptor serves as a parent and carries a nitrogen-containing heterocyclic substitution group.

[0029] The sulfur-phosphorus heterocyclic receptor and nitrogen-containing heterocyclic donor compound have the following structure:

[0030]

[0031] Wherein, R1 and R2 are selected from nitrogen-containing heterocyclic substituents or hydrogen, and the nitrogen-containing heterocyclic substituents are selected from 9,9-dimethylacridin-N-yl, 9,9-diphenylacridin-N-yl, N-phenothiazinyl or N-phenoxazinyl; R2 is selected from nitrogen-containing heterocyclic substituents, preferably selected from N-dimethylacridinyl, N-diphenylacridinyl, N-phenothiazinyl or N-phenoxazinyl.

[0032] Preferably, the sulfur-phosphorus heterocyclic acceptor and nitrogen-containing heterocyclic donor compound are selected from:

[0033]

[0034] The sulfur-phosphorus heterocyclic acceptor and nitrogen-containing heterocyclic donor compound provided in the present invention have good ICT capability, improve RISC efficiency, and utilize the steric effect of the phosphine oxygen group to inhibit the relaxation of the excited state structure and the exciton quenching caused by the intermolecular interaction, thereby improving the photoluminescence quantum yield as a thermally excited delayed fluorescent luminescent material, thereby achieving an improvement in the luminescence efficiency of the device.

[0035] In addition, the sulfur-phosphorus heterocyclic acceptor and nitrogen-containing heterocyclic donor compound provided in the present invention also have good thermal stability, so that the stability of the device is also improved. As the guest material of the light-emitting layer, the current efficiency and power efficiency of the electroluminescent device are effectively improved.

[0036] The sulfur-phosphorus heterocyclic acceptor and nitrogen-containing heterocyclic donor compound are prepared by carbon-nitrogen coupling reaction of a halogenated sulfur-phosphorus heterocyclic compound and a nitrogen-containing heterocyclic compound under the action of a palladium catalyst.

[0037] The halogenated sulfur-phosphorus heterocyclic compound is:

[0038]

[0039] Wherein, X1 is independently selected from H, Cl, Br or I, preferably selected from H, Cl or Br, more preferably H or Br; X2 is selected from Cl, Br or I, preferably selected from Cl or Br, more preferably Br.

[0040] The nitrogen-containing heterocyclic compound is selected from 9,9-dimethylacridine (DMAC), 9,9-diphenylacridine (DPAC), phenothiazine (PTZ) or phenoxazine (PXZ).

[0041] The second aspect of the present invention provides a preparation method based on a sulfur-phosphorus heterocyclic acceptor and a nitrogen-containing heterocyclic donor compound, wherein the method is prepared by a carbon-nitrogen coupling reaction of a halogenated sulfur-phosphorus heterocyclic compound and a nitrogen-containing heterocyclic compound in the presence of a palladium catalyst in an alkaline environment.

[0042] The method comprises the following steps:

[0043] Step 1, preparing a halogenated sulfur-phosphorus heterocyclic compound. Specifically comprising the following steps:

[0044] Step 1-1, using diphenyl sulfide and phenylphosphine dichloride as raw materials, in the presence of alkyl lithium, the following heterocyclic compound is prepared:

[0045]

[0046] The alkyl lithium is selected from n-butyl lithium, methyl lithium, phenyl lithium, preferably n-butyl lithium.

[0047] The molar ratio of diphenyl sulfide to phenylphosphine dichloride is 1:(1-1.5), preferably 1:(1-1.2). The molar ratio of diphenyl sulfide to alkyl lithium is 1:(2-3.5), preferably 1:(2-2.5).

[0048] In step 1-1, the reaction temperature is -10 to 5°C, preferably -5 to 2°C, and the reaction time is 10 to 25 hours, preferably 15 to 18 hours.

[0049] After the reaction is completed, the mixture is extracted with water and dichloromethane, dried with a solid desiccant, and the solvent is dried by spin drying.

[0050] Step 1-2, oxidizing the heterocyclic compound obtained in step 1-1 to obtain the following oxidized sulfur-phosphorus heterocyclic compound,

[0051]

[0052] The oxidation is to add an oxidant to the solvent in which the heterocyclic compound obtained in step 1-1 is dissolved. The oxidant is selected from hydrogen peroxide or peracetic acid, preferably hydrogen peroxide, and more preferably a hydrogen peroxide aqueous solution with a mass fraction of 25%-35%.

[0053] The reaction is carried out in a solvent, the solvent is selected from one or more of a halogenated hydrocarbon solvent, an aromatic hydrocarbon solvent and an amide solvent, preferably a halogenated hydrocarbon solvent, more preferably dichloromethane. The volume molar ratio of dichloromethane to diphenyl sulfide in step 1-1 is (6-18) mL:1 mol, preferably (8-15) mL:1 mol, more preferably (10-12) mL:1 mol.

[0054] In step 1-2, the reaction temperature is -10 to 5°C, preferably -5 to 2°C, and the reaction time is 3 to 8 hours, preferably 4 to 6 hours.

[0055] After the reaction is completed, the mixture is extracted with water and dichloromethane, dried with a solid desiccant, and the solvent is dried by spin drying.

[0056] Step 1-3, halogenating the oxidized sulfur-phosphorus heterocyclic compound obtained in step 1-2 to obtain the following halogenated sulfur-phosphorus heterocyclic compound,

[0057]

[0058] The halogenation is carried out in a solvent, the solvent is selected from an acidic organic solvent, preferably an alkyl acid, more preferably glacial acetic acid, and the volume molar ratio of the solvent to the oxidized sulfur-phosphorus heterocyclic compound obtained in step 1-2 is (2-12) mL:1 mmol, preferably (3-9) mL:1 mmol, and more preferably (4-6) mL:1 mmol.

[0059] The reaction is carried out in the presence of 98 wt % concentrated sulfuric acid, and the volume molar ratio of the concentrated sulfuric acid to the oxidized sulfur-phosphorus heterocyclic compound obtained in step 1-2 is (0.8-2.1) mL:1 mmol, preferably (1-1.8) mL:1 mmol, and more preferably (1.2-1.5) mL:1 mmol.

[0060] The halogenation is carried out in the presence of a halogenating agent, and the molar ratio of the halogenating agent to the oxidized sulfur-phosphorus heterocyclic compound obtained in step 1-2 is (0.8-3): 1 or (3-10): 1, preferably (1-2.5): 1 or (4-6): 1. The halogenating agent is preferably a brominating agent, such as N-bromosuccinimide (NBS).

[0061] After the reaction, the product was poured into an ice-water bath, extracted with dichloromethane, dried with a solid desiccant, and spin-dried. A mixed solvent of ethyl acetate (EA) and petroleum ether (PE) (volume ratio EA:PE=2:1) ​​was used as an eluent for column chromatography purification to obtain a halogenated phosphorus-sulfur heterocyclic compound.

[0062] Step 2: adding a halogenated sulfur-phosphorus heterocyclic compound, a nitrogen-containing heterocyclic donor compound, a palladium catalyst and an alkaline substance into a reaction solvent, stirring for reaction, and obtaining a reaction solution.

[0063] The alkaline substance is selected from one or more of alkali metal hydroxides, potassium alcoholates and sodium alcoholates, preferably one or more of NaOH, KOH, potassium tert-butoxide and sodium tert-butoxide, more preferably potassium tert-butoxide and / or sodium tert-butoxide, such as potassium tert-butoxide.

[0064] The reaction solvent is selected from one or more of aromatic hydrocarbon solvents, amide solvents and ketone solvents, preferably one or more of toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, cyclohexanone, methyl ethyl ketone, more preferably xylene.

[0065] The palladium catalyst is selected from palladium salts, such as palladium chloride or palladium acetate, palladium carbon, palladium supported on inorganic oxides, such as Pd / Al2O3 or Pd / MgO, palladium complexes, such as Pd(AsPh3)4, di(tri-tert-butylphosphine)palladium, tetrakis(triphenylphosphine)palladium, Pd((MeO)3P)4, preferably palladium salts or palladium complexes, more preferably palladium acetate and / or di(tri-tert-butylphosphine)palladium.

[0066] The molar ratio of the halogenated sulfur-phosphorus heterocyclic compound to the nitrogen-containing heterocyclic donor compound is 1:(1.5-7.5), preferably 1:(2.0-7.0), more preferably 1:(2.5-6.5), such as 1:6 or 1:3.

[0067] The molar ratio of the halogenated sulfur-phosphorus heterocyclic compound to the alkaline substance is 1:(3.5-8.5), preferably 1:(4.5-7.5), and more preferably 1:(5.5-6.5).

[0068] The molar ratio of the halogenated sulfur-phosphorus heterocyclic compound to the palladium catalyst is 1:(0.006-0.035), preferably 1:(0.008-0.025), and more preferably 1:(0.01-0.015).

[0069] The molar volume ratio of the halogenated sulfur-phosphorus heterocyclic compound to the reaction solvent is 1 mmol:(5-18) mL, preferably 1 mmol:(7-15) mL, and more preferably 1 mmol:(8-12) mL.

[0070] The coupling reaction is carried out under a protective atmosphere, such as nitrogen or argon atmosphere, at a reaction temperature of 115-150° C., preferably 120-140° C., more preferably 125-135° C., and for a reaction time of 6-15 hours, preferably 8-12 hours, such as 10 hours.

[0071] Step 3: post-treating the reaction solution to obtain a sulfur-phosphorus heterocyclic receptor and a nitrogen-containing heterocyclic donor compound.

[0072] After the reaction in step 2 is completed, the obtained reaction solution is poured into ice water to quench the reaction. After standing and stratification, the organic layer is separated, the organic layer is dried using a solid desiccant, and then purified by column chromatography using a mixed solvent of dichloromethane and petroleum ether as an eluent, preferably, the volume ratio of dichloromethane to petroleum ether is 2:1, to obtain a sulfur-phosphorus heterocyclic receptor and a nitrogen-containing heterocyclic donor compound.

[0073] The molecular synthesis route based on the sulfur-phosphorus heterocyclic receptor and the nitrogen-containing heterocyclic donor compound in the present invention is reasonably designed, the synthesis method is easy to carry out, and the target product can be obtained.

[0074] The third aspect of the present invention provides the use of the sulfur-phosphorus heterocyclic acceptor and the nitrogen-containing heterocyclic donor compound as the light-emitting layer material to prepare an electroluminescent device according to the first aspect.

[0075] The fourth aspect of the present invention provides an electroluminescent device, wherein the light-emitting layer material of the electroluminescent device comprises the sulfur-phosphorus heterocyclic acceptor and the nitrogen-containing heterocyclic donor compound.

[0076] The electroluminescent device further comprises a conductive anode layer, a hole injection layer, a hole transport layer, an electron transport layer, an electron injection layer and a cathode conductive layer.

[0077] The present invention provides a method for preparing a light-emitting device using the sulfur-phosphorus heterocyclic acceptor and the nitrogen-containing heterocyclic donor compound as light-emitting layer materials, which specifically comprises the following steps:

[0078] 1. preparing a conductive anode layer;

[0079] The conductive anode layer is prepared on the substrate layer. The conductive anode layer is selected from tin oxide conductive glass (ITO), transparent conductive polymers such as polyaniline, and semi-transparent metals such as Au, preferably ITO or semi-transparent metals, more preferably ITO. Preferably, the conductive anode layer is evaporated by vacuum evaporation.

[0080] Preferably, the vacuum degree of vacuum evaporation is 1×10 -6 mbar, the evaporation rate is set to 0.1-0.3 nm / s, the evaporation material is indium tin oxide on the glass or plastic substrate, and the thickness of the anode conductive layer is 6-40 nm, preferably 8-30 nm, and more preferably 10-20 nm.

[0081] Preferably, the following hole injection layer, hole transport layer, light emitting layer, electron transport layer, electron injection layer and cathode conductive layer are prepared by vacuum evaporation method.

[0082] 2. preparing a hole injection layer;

[0083] The hole injection layer is evaporated on the anode conductive layer, and the evaporated thickness is 4 to 35 nm, preferably 6 to 25 nm, more preferably 8 to 15 nm, such as 10 nm.

[0084] The hole injection layer material is selected from molybdenum oxide or poly (3,4-ethylenedioxythiophene): polystyrene sulfonate) (PEDOT:PSS), preferably molybdenum oxide, more preferably molybdenum oxide, such as MoO3.

[0085] 3. Preparation of hole transport layer;

[0086] The hole transport layer is evaporated on the hole injection layer, and the evaporated thickness is 15-55 nm, preferably 20-45 nm, more preferably 25-35 nm, such as 30 nm.

[0087] The hole transport layer material is selected from one or more of aromatic amine compounds and carbazole compounds, such as N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), 9,9'-(1,3-phenyl)di-9H-carbazole (mCP), preferably mCP.

[0088] 4. preparing a light-emitting layer;

[0089] The light-emitting layer is continuously evaporated on the hole transport layer, and the evaporated thickness is 35-75 nm, preferably 40-65 nm, more preferably 45-55 nm, such as 50 nm.

[0090] The light-emitting layer material includes a sulfur-phosphorus heterocyclic acceptor and a nitrogen-containing heterocyclic donor compound, preferably, also includes 4,6-diphenylphosphineoxydibenzofuran (DBFDPO). The mass fraction of the sulfur-phosphorus heterocyclic acceptor and the nitrogen-containing heterocyclic donor compound in the light-emitting layer material is 10-30%, preferably 15-25%, such as 20%.

[0091] 5. preparing an electron transport layer;

[0092] The electron transport layer material is selected from one or more of tris(8-hydroxyquinoline)aluminum (Alq3), 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 4,7-diphenyl-1,10-phenanthroline (Bphen), 3-(biphenyl-4-yl)-5-(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole (TAZ), di[2-((oxy)diphenylphosphino)phenyl]ether (DPEPO) and 4,6-diphenylphosphinooxydibenzofuran (DBFDPO), preferably DBFDPO. The electron transport layer is evaporated on the light-emitting layer, and the evaporation thickness is 25-55nm, more preferably 35-45nm, such as 40nm.

[0093] 6. preparing an electron injection layer;

[0094] The electron injection layer is evaporated on the electron transport layer, and the evaporated thickness is 4-18 nm, preferably 6-15 nm, more preferably 8-12 nm, such as 10 nm.

[0095] The electron injection layer material is selected from lithium tetrakis(8-hydroxyquinoline)borate (LiBq4) or LiF, preferably LiF.

[0096] 7. Prepare a cathode conductive layer, encapsulate it, and obtain a thermally excited delayed fluorescence electroluminescent device.

[0097] The cathode conductive layer is evaporated on the electron injection layer, and the evaporated thickness is 60-130 nm, preferably 70-120 nm, more preferably 80-110 nm, such as 100 nm.

[0098] The cathode conductive layer material is selected from a single metal cathode or an alloy cathode, such as metal Al.

[0099] The pyrolysis temperature of the compound (I) and the compound (II) in the present invention can reach above 360°C, preferably above 400°C. The current efficiency of the electroluminescent device reaches a maximum value of 45-65cd·A at the luminescence peak of about 500-510nm. -1 , preferably 64.5cd·A -1 , the power efficiency reaches a maximum of 50-80lm·W -1 , preferably 75.1lm·W -1 , the maximum external quantum efficiency is 20-28%, preferably 22-26.5%, and the turn-on voltage is lower than 3V, preferably 2.7V.

[0100] The pyrolysis temperature of compound (III) and compound (IV) in the present invention can reach above 410°C, preferably above 440°C. The current efficiency of the electroluminescent device reaches a maximum value of 70-90 cd·A at the luminescence peak of about 500-510 nm.-1 , preferably 89.9 cd·A -1 , the power efficiency reaches a maximum of 80-109lm·W -1 , preferably 108.6lm·W -1 , the maximum external quantum efficiency is 20-28%, preferably 27.2%, and the turn-on voltage is lower than 3V, preferably 2.6V.

[0101] The pyrolysis temperature of the compound (V) and the compound (VI) in the present invention can reach above 460°C, preferably above 480°C. The current efficiency of the electroluminescent device reaches a maximum value of 60-70 cd·A at the luminescence peak position of 490-500 nm. -1 , preferably 65.9 cd·A -1 , the power efficiency reaches a maximum of 70-80lm·W -1 , preferably 78.1 lm·W -1 , the maximum external quantum efficiency is 18-25%, preferably 22.7%, and the turn-on voltage is lower than 3V, preferably 2.6V.

[0102] The pyrolysis temperature of compound (VII) and compound (VIII) in the present invention can reach above 360°C, preferably above 420°C. The current efficiency of the electroluminescent device reaches a maximum value of 60-70 cd·A at the luminescence peak position of 495-505 nm. -1 , preferably 66.9 cd·A -1 , the power efficiency reaches a maximum value of 75-85, preferably 82.4lm·W -1 , the maximum external quantum efficiency is 18-25%, preferably 22.1%, and the turn-on voltage is lower than 3V, preferably 2.5V.

[0103] Example

[0104] Example 1

[0105] (1) 1 mmol of diphenyl sulfide (DPS), 2.4 mmol of n-butyl lithium and 1 mmol of phenylphosphine dichloride were mixed and reacted in an ice-water bath for 16 hours. After the reaction, the mixture was extracted with 10 ml of water and 10 ml of dichloromethane, dried over anhydrous sodium sulfate and the solvent was dried by spin drying.

[0106] The obtained solid was dissolved with 10 ml of dichloromethane, and 10-15 mmol of hydrogen peroxide (concentration: 30 wt%) was added in an ice-water bath, and reacted for 4 hours, and then extracted with 10 mL of water and 10 mL of dichloromethane, and dried over anhydrous sodium sulfate. The solvent was spin-dried.

[0107] The obtained 1mmol solid was placed in a single-necked bottle, and 4ml glacial acetic acid, 1.2ml concentrated sulfuric acid (98wt%), and 6mmol N-bromosuccinimide (NBS) were added, and the reaction was carried out at 30°C for 10 hours. After the reaction, the product was poured into an ice-water bath, extracted with dichloromethane, dried over anhydrous sodium sulfate, and spin-dried. A mixed solvent of ethyl acetate and petroleum ether (volume ratio EA:PE=2:1) ​​was used as an eluent for column chromatography purification to obtain the following dibromothiophosphorus heterocyclic compound.

[0108]

[0109] (2) 1 mmol of a dibromothiophosphine heterocyclic compound having the above structure, 6 mmol of 9,9-dimethylacridine (DMAC), 6 mmol of potassium tert-butoxide, 6 mmol of tri-tert-butylphosphine, 0.01 mmol of palladium acetate and 10 ml of xylene were mixed, reacted for 10 hours, poured into ice water, and extracted with 10 ml of dichloromethane to obtain an organic layer. After adding anhydrous sodium sulfate to dry the organic layer, the organic layer was purified by column chromatography using a mixed solvent of dichloromethane and petroleum ether as an eluent, wherein the volume ratio of dichloromethane to petroleum ether was 2:1, to obtain compound (I) (SOSPODMAC2), which is:

[0110]

[0111] The NMR test results of compound (I) are as follows:

[0112] 1 H NMR (TMS, CDCl3, 400MHz): δ = 8.534-8.473 (m, 2H), 8.453-8.404 (m, 2H), 7.988-7.869 (m, 2H), 7. 645-7.582(m,1H),7.571-7.475(m,8H),7.073-6.999(m,8H),6.384-6.303(m,4H); 1.5(s,12H).

[0113] Laser desorption ionization time-of-flight mass spectrometry (LDI-TOF-MS) test results are: m / z (%): 738.89 (100) [M + ].

[0114] The results of elemental analysis are (%) (C 48 H 39 N2O2PS): C, 78.03; H, 5.32; N, 3.79; O, 4.33; P, 4.19; S, 4.34.

[0115] The UV, fluorescence and phosphorescence spectra of compound (I) were tested. Figure 1 shown.

[0116] Thermogravimetric analysis of compound (I) showed that its pyrolysis temperature was 407°C.

[0117] (3) Preparation of electroluminescent devices using compound (I):

[0118] 1. Place the plastic substrate cleaned with deionized water into a vacuum evaporator with a vacuum degree of 1×10 -6 mbar, and the evaporation rate was set to 0.1 nm s -1 , an anode conductive layer with a thickness of 10 nm and indium tin oxide (ITO) is deposited on a glass or plastic substrate;

[0119] 2. Evaporating the hole injection layer material MoO3 on the anode conductive layer to obtain a hole injection layer with a thickness of 10 nm;

[0120] 3. Evaporating the hole transport layer material mCP on the hole injection layer to obtain a hole transport layer with a thickness of 30 nm;

[0121] 5. Evaporating a light-emitting layer on the hole transport layer, the material of which is a mixture of compound (I) and DBFDPO, the mass fraction of compound (I) in the mixture is 20%, and the thickness is 50 nm;

[0122] 6. Continue to evaporate the electron transport layer DBFDPO on the light-emitting layer, with a thickness of 40nm;

[0123] 8. Vapor depositing electron injection layer material LiF on the electron transport layer to form an electron injection layer with a thickness of 10 nm;

[0124] 9. Aluminum was evaporated on the electron injection layer to form a cathode conductive layer with a thickness of 100 nm, thereby obtaining device 1.

[0125] The structure of device 1 is: ITO / MoO3 (10nm) / mCP (30nm) / DBFDPO: (Ⅰ) (20%) (50nm) / DBFDPO (40nm) / LiF (10nm) / Al.

[0126] The voltage-current density relationship curve of the test device 1 is as follows: Figure 2 As shown, it can be seen that compound (I) has semiconductor properties and its threshold voltage is 2.7V.

[0127] From the variation trend of the brightness of the test device 1 with the voltage, it can be seen that the start-up voltage of the device is 2.7V.

[0128] The variation trend of the current efficiency of device 1 with the brightness is tested. It can be seen that when the brightness of device 1 is 54.2 cd·m -2 When the current efficiency reaches the maximum value of 47cd·A -1 .

[0129] The power efficiency of device 1 changes with the brightness. It can be seen that when the brightness is 130 cd·m -2 When the power efficiency reaches the maximum value of 55lm·W -1 .

[0130] The variation trend of the external quantum efficiency of device 1 with the brightness is tested. It can be seen that device 1 has a brightness of 11.6 cd·cm -2 When , the maximum external quantum efficiency of 26.5% is obtained.

[0131] The electroluminescence spectrum of device 1 was tested, and it was found that the electroluminescence peak of device 1 was 507 nm.

[0132] Example 2

[0133] (1) 1 mmol of diphenyl sulfide (DPS), 2.4 mmol of n-butyl lithium and 1 mmol of phenylphosphine dichloride were mixed and reacted in an ice-water bath for 16 hours. After the reaction, the mixture was extracted with 10 ml of water and 10 ml of dichloromethane, dried over anhydrous sodium sulfate and the solvent was dried by spin drying.

[0134] The obtained solid was dissolved with 10 ml of dichloromethane, 10-15 mmol of hydrogen peroxide was added in an ice-water bath, reacted for 4 hours, extracted with 10 mL of water and 10 mL of dichloromethane, dried over anhydrous sodium sulfate, and the solvent was dried by spin drying.

[0135] The obtained 1 mmol solid was placed in a single-necked bottle, and 4 ml of glacial acetic acid, 1.2 ml of concentrated sulfuric acid, and 1 mmol of N-bromosuccinimide (NBS) were added, and the reaction was carried out at 30°C for 10 hours. After the reaction, the product was poured into an ice-water bath, extracted with dichloromethane, dried with anhydrous sodium sulfate, and spin-dried, and purified by column chromatography with an eluent of EA:PE=2:1.

[0136]

[0137] (2) Compound (II) was prepared according to the method of Example 1, except that the dibrominated thiophosphorus heterocyclic compound in Example 1 was replaced by an equimolar amount of the monobrominated thiophosphorus heterocyclic compound having the above structure, and the amount of DMAC added was 3 mmol.

[0138]

[0139] The NMR test results of compound (II) are as follows:

[0140] 1H NMR (TMS, CDCl3, 400MHz): δ = 8.529-8.423 (m, 2H), 8.372-8.303 (m, 1H), 8.219-8.157 (m, 1H), 7.917-7.859 (m, 1H), 7. 848-7.792(m,2H),7.580-7.524(m,1H),7.511-7.413(m,6H),7.010-6.946(m,4H),6.272-6.205(m,2H),1.5(s,6H).

[0141] Laser desorption ionization time-of-flight mass spectrometry (LDI-TOF-MS) test results are: m / z (%): 531.61 (100) [M + ].

[0142] The results of elemental analysis are (%) (C 33 H 26 NO2PS): C, 74.56; H, 4.93; N, 2.63; O, 6.02; P, 5.83; S, 6.03.

[0143] The compound (II) was tested by UV, fluorescence and phosphorescence spectra. Figure 3 shown.

[0144] Thermogravimetric analysis of compound (II) showed that its pyrolysis temperature was 366°C.

[0145] Device 2 was prepared according to the method in Example 1, and the structure of Device 2 was: ITO / MoO3 (10nm) / mCP (30nm) / DBFDPO: (Ⅱ) (20%) (50nm) / DBFDPO (40nm) / LiF (10nm) / Al.

[0146] The voltage-current density relationship curve of the test device 2 is as follows: Figure 4 As shown, it can be seen that compound (II) has semiconductor properties and its threshold voltage is 2.6V.

[0147] From the variation trend of the brightness of device 2 with the voltage, we can know that the start-up voltage of the device is 2.7V.

[0148] The variation trend of the current efficiency of device 2 with the brightness is tested. It can be seen that device 2 has a brightness of 1.05 cd·m -2 When the current efficiency reaches the maximum value of 64.5cd·A -1 .

[0149] The power efficiency of device 2 changes with the brightness. It can be seen that device 2 has a brightness of 1.05 cd·m -2 When the power efficiency reaches the maximum value of 75.1lm·W-1 .

[0150] The variation trend of the external quantum efficiency of device 2 with the brightness is tested. It can be seen that device 2 has a brightness of 1.05 cd·cm -2 When , the maximum external quantum efficiency of 22.0% is obtained.

[0151] The electroluminescence spectrum of device 2 was tested, and it was found that the electroluminescence peak of device 2 was 503 nm.

[0152] Example 3

[0153] Compound (III) was prepared according to the method of Example 1, except that 6 mmol of 9,9-diphenylacridine (DPAC) was added to replace DMAC.

[0154]

[0155] The NMR test results of compound (III) are as follows:

[0156] 1 H NMR (TMS, CDCl3, 400MHz): δ=8.254-8.174(m,4H),7.579-7.539(m,3H),7.483-7.402(m ,4H),7.276-7.259(d,J=6.8Hz,13H),7.145-7.103(m,4H),7.005-6.964(q,J1=1.6Hz,J 2=7.2Hz,16H),6.516-6.496(d,J=8.0Hz,3H).

[0157] The laser desorption ionization time-of-flight mass spectrometry (LDI-TOF-MS) test results are: m / z (%): 987.17 (100) [M+].

[0158] Elemental analysis test results (%), C 68 H 47 N2O2PS: C, 82.74; H, 4.80; N, 2.84; O, 3.24; P, 3.14; S, 3.254.

[0159] The compound (III) was tested by UV, fluorescence and phosphorescence spectra. Figure 5 shown.

[0160] Thermogravimetric analysis of compound (III) showed that its pyrolysis temperature was 445°C.

[0161] Device 3 was prepared according to the Chinese method in Example 1. The structure of device 3 was: ITO / MoO3 (10 nm) / mCP (30 nm) / DBFDPO: (III) (20%) (50 nm) / DBFDPO (40 nm) / LiF (10 nm) / Al.

[0162] The voltage-current density relationship curve of the test device 3 is as follows: Figure 6 As shown, it can be seen that compound (III) has semiconductor properties and its threshold voltage is 2.7V.

[0163] From the variation trend of the brightness of device 3 with the voltage, we can know that the start-up voltage of the device is 2.7V.

[0164] The variation trend of the current efficiency of device 3 with the brightness is tested. It can be seen that device 3 has a brightness of 1.65 cd·m -2 When the current efficiency reaches the maximum value of 70.4cd·A -1 .

[0165] The power efficiency of device 3 changes with the brightness. It can be seen that device 3 has a brightness of 1.65 cd·m -2 When the power efficiency reaches the maximum value of 81.2lm·W -1 .

[0166] The variation trend of the external quantum efficiency of device 3 with the brightness is tested. It can be seen that device 3 has a brightness of 1.75 cd·m -2 When , the maximum external quantum efficiency of 21.0% is obtained.

[0167] The electroluminescence spectrum of device 3 was tested, and it was found that the electroluminescence peak of device 3 was 506 nm.

[0168] Example 4

[0169] Compound (IV) was prepared according to the method of Example 2, except that an equal molar amount of DPAC was added to replace DMAC.

[0170]

[0171] The NMR test results of compound (IV) are as follows:

[0172] 1H-NMR (TMS, CDCl3, 400MHz): δ=8.479-8.227(m,1H),8.222-7.898(m,2H),7.879-7.557(m,2H),7.552-7.496(m,1H),7.4 92-7.280 (m, 5H), 7.276-7.101 (t, J = 5.6Hz, 7H), 7.095-7.009 (m, 2H), 7.004-6.946 (m, 8H), 6.451-6.431 (d, J = 8.0Hz, 2H).

[0173] Laser desorption ionization time-of-flight mass spectrometry (LDI-TOF-MS) test results are: m / z (%): 655.75 (100) [M + ].

[0174] Elemental analysis test results (%) C 43 H 30 NO2PS: C, 78.76; H, 4.61; N, 2.14; O, 4.88; P, 4.72; S, 4.89.

[0175] The compound (Ⅳ) was tested by UV, fluorescence and phosphorescence spectra. Figure 7 shown.

[0176] Thermogravimetric analysis of compound (IV) showed that its pyrolysis temperature was 410°C.

[0177] Device 4 was prepared according to the method in Example 3, and the structure of device 4 was: ITO / MoO3 (10nm) / mCP (30nm) / DBFDPO: (IV) (20%) (50nm) / DBFDPO (40nm) / LiF (10nm) / Al.

[0178] The voltage-current density relationship curve of the test device 4 is as follows: Figure 8 As shown, it can be seen that compound (IV) has semiconductor properties and its threshold voltage is 2.6V.

[0179] From the variation trend of the brightness of device 4 with the voltage, we can know that the start-up voltage of the device is 2.6V.

[0180] The variation trend of the current efficiency of device 4 with the brightness is tested. It can be seen that device 4 has a brightness of 1.48 cd·m -2 When the current efficiency reaches the maximum value of 89.9cd·A -1 .

[0181] The power efficiency of device 4 changes with brightness. It can be seen that the device has a brightness of 1.48 cd·m -2 When the power efficiency reaches the maximum value of 108.6lm·W-1 .

[0182] The variation trend of the external quantum efficiency of device 4 with the brightness shows that the device has a brightness of 1.48 cd·m -2 When , the maximum external quantum efficiency of 27.2% is obtained.

[0183] The electroluminescence spectrum of the test device 4 shows that the electroluminescence peak of the device is at 505 nm.

[0184] Example 5

[0185] Compound (V) was prepared according to the method of Example 1, except that DMAC was replaced by an equimolar amount of phenothiazine (PTZ).

[0186]

[0187] The NMR test results of compound (V) are as follows:

[0188] 1 H NMR (TMS, CDCl3, 400MHz): δ = 8.594 (d, J = 11.6Hz, 4H), 7.848 (t, J = 11.6Hz, 4H), 7.610-7.539 (m, 9H), 7.456 (t, J = 8.4Hz, 5H), 7.345ppm (d, J = 7.2Hz, 5H).

[0189] The test results of laser desorption ionization time-of-flight mass spectrometry (LDI-TOF-MS) were: m / z (%): 718.84 (100) [M+].

[0190] The elemental analysis test results are (%) C 42 H 27 N2O2PS3:C,70.18;H,3.79;N,3.90;O,4.45;P,4.31;S,13.38.

[0191] The compound (V) was tested by UV, fluorescence and phosphorescence spectra. Fig. 9 shown.

[0192] Thermogravimetric analysis of compound (V) revealed that its pyrolysis temperature was 488°C.

[0193] Device 5 was prepared according to the method in Example 1: ITO / MoO3 (10 nm) / mCP (30 nm) / DBFDPO: (V) (20%) (50 nm) / DBFDPO (40 nm) / LiF (10 nm) / Al.

[0194] The voltage-current density relationship curve of the test device 5 is as follows: Fig.10 As shown, it can be seen that compound (V) has semiconductor characteristics and its threshold voltage is 2.6V.

[0195] The variation trend of the brightness of device 5 with respect to voltage is tested, and it can be known that the start-up voltage of the device is 2.6V.

[0196] The variation trend of the current efficiency of device 5 with the brightness is shown in the figure. It can be seen that the device has a brightness of 1.3 cd·m -2 When the current efficiency reaches the maximum value of 65.8cd·A -1 .

[0197] The power efficiency of device 5 changes with the brightness. It can be seen that the device is at a brightness of 1.3 cd·m -2 When the power efficiency reaches the maximum value of 74.6lm·W -1 .

[0198] The variation trend of the external quantum efficiency of device 5 with the brightness shows that the device has a brightness of 1.3 cd·m -2 The maximum external quantum efficiency of 19.9% ​​was obtained.

[0199] The electroluminescence spectrum of the tested device 5 shows that the electroluminescence peak of the device is 498 nm.

[0200] Example 6

[0201] Compound (VI) was prepared according to the method of Example 2, except that DMAC was replaced by an equimolar amount of phenothiazine (PTZ).

[0202]

[0203] The NMR test results of compound (VI) are as follows: 1 H-NMR (TMS, CDCl3, 400MHz): δ = 7.055-6.969 (m, 7H), 6.855-6.838 (m, 4H), 6.799-6.765 (m, 4H), 6.281-6.262 (d, J = 7.6Hz, 4H) 5.293ppm (s, 1H).

[0204] Laser desorption ionization time-of-flight mass spectrometry (LDI-TOF-MS) test results are: m / z (%): 521.07 (100) [M + ].

[0205] Elemental analysis test results (%) C 30 H 20 NO2PS2:C,69.08;H,3.87;N,2.69;O,6.13;P,5.94;S,12.29.

[0206] The compound (VI) was tested by UV, fluorescence and phosphorescence spectra. Fig.11 shown.

[0207] Thermogravimetric analysis of compound (VI) showed that its pyrolysis temperature was 478°C.

[0208] Device 6 was prepared according to the method in Example 5: ITO / MoO3 (10 nm) / mCP (30 nm) / DBFDPO: (VI) (20%) (50 nm) / DBFDPO (40 nm) / LiF (10 nm) / Al.

[0209] The voltage-current density relationship curve of the test device 6 is as follows: Fig.12 As shown, it can be seen that compound (VI) has semiconductor properties and its threshold voltage is 2.6V.

[0210] From the variation trend of the brightness of the tested device 6 with the voltage, it can be seen that the start-up voltage of the device is 2.6V.

[0211] The variation trend of the current efficiency of device 6 with the brightness shows that the brightness of the device is 1.42 cd·m -2 When the current efficiency reaches the maximum value of 65.9cd·A -1 .

[0212] The power efficiency of device 6 varies with brightness. It can be seen that the device has a brightness of 1.42 cd·m -2 When the power efficiency reaches the maximum value of 78.1lm·W -1 .

[0213] The variation trend of the external quantum efficiency of device 6 with the brightness shows that the device has a brightness of 1.42 cd·m -2 When , the maximum external quantum efficiency of 22.7% is obtained.

[0214] The electroluminescence spectrum of the test device 6 shows that the electroluminescence peak of the device is at 493 nm.

[0215] Example 7

[0216] Compound (VII) was prepared according to the method of Example 1, except that an equal molar amount of phenoxazine (PXZ) was added instead of DMAC.

[0217]

[0218] The NMR test results of compound (VII) are as follows:

[0219] 1H NMR (TMS, CDCl3, 400MHz): δ = 8.514-8.512 (d, J = 0.8Hz, 2H), 8.374-8.342 (m, 2H), 7.899-7.8 79(d,J=8Hz,2H),7.592-7.462(m,6H),6.660-6.624(m,4H),6.002-5.982ppm(d,J=8Hz,4H).

[0220] The laser desorption ionization time-of-flight mass spectrometry (LDI-TOF-MS) test results were: m / z (%): 686.72 (100) [M+].

[0221] Elemental analysis test results (%) C 42 H 27 N2O4PS: C, 73.46; H, 3.96; N, 4.08; O, 9.32; P, 4.51; S, 4.67.

[0222] The UV, fluorescence and phosphorescence spectra of compound (VII) are tested. Fig.13 shown.

[0223] Thermogravimetric analysis of compound (VII) showed that its pyrolysis temperature was 429°C.

[0224] Device 7 was prepared according to the method in Example 1: ITO / MoO3 (10nm) / mCP (30nm) / DBFDPO: (VII) (20%) (50nm) / DBFDPO (40nm) / LiF (10nm) / Al.

[0225] The voltage-current density relationship curve of the test device 7 is as follows: Fig.14 As shown, it can be seen that compound (VII) has semiconductor properties and its threshold voltage is 2.5V.

[0226] From the variation trend of the brightness of the tested device 7 with the voltage, it can be seen that the start-up voltage of the device is 2.5V.

[0227] The variation trend of the current efficiency of device 7 with the brightness is shown in the figure. It can be seen that the device has a brightness of 1.15 cd·m -2 When the current efficiency reaches the maximum value of 66.9cd·A -1 .

[0228] The power efficiency of device 7 varies with brightness. It can be seen that the device has a brightness of 1.15 cd·m -2 When the power efficiency reaches the maximum value of 82.4lm·W -1 .

[0229] The variation trend of the external quantum efficiency of device 7 with the brightness shows that the device has a brightness of 1.15 cd·m -2 When , the maximum external quantum efficiency of 22.1% is obtained.

[0230] The electroluminescence spectrum of the test device 7 shows that the electroluminescence peak of the device is at 504 nm.

[0231] Example 8

[0232] Compound (VIII) was prepared according to the method of Example 2, except that an equal molar amount of phenoxazine (PXZ) was added instead of DMAC.

[0233]

[0234] The NMR test results of compound (VIII) are as follows:

[0235] 1H-NMR (TMS, CDCl3, 400MHz): δ=8.475-8.424(m,2H),8.333-8.282(m,1H),8.180-8.151(m,1H),7.893-7.813(m,3H),7.683-7.630(m,1H),7. 553-7.540(m,1H),7.480-7.429(m,3H),6.792-6.595(m,5H),6.055-6 .036(d,J=7.6Hz,1H),5.935-5.916(d,J=7.6Hz,1H),5.297ppm(s,1H).

[0236] Laser desorption ionization time-of-flight mass spectrometry (LDI-TOF-MS) test results are: m / z (%): 505.53 (100) [M + ].

[0237] Elemental analysis test results (%) C 30 H 20 NO3PS:C,71.28;H,3.99;N,2.77;O,9.49;P,6.13;S,6.34.

[0238] The compound (VIII) was tested by UV, fluorescence and phosphorescence spectra. Fig.15 shown.

[0239] Thermogravimetric analysis of compound (VIII) showed that its pyrolysis temperature was 369°C.

[0240] Device 8 was prepared according to the method in Example 7: ITO / MoO3 (10nm) / mCP (30nm) / DBFDPO: (VIII) (20%) (50nm) / DBFDPO (40nm) / LiF (10nm) / Al.

[0241] The voltage-current density relationship curve of the test device 8 is as follows: Fig.16 As shown, it can be seen that compound (VIII) has semiconductor properties and its threshold voltage is 2.5V.

[0242] From the variation trend of the brightness of the tested device 8 with the voltage, it can be seen that the start-up voltage of the device is 2.5V.

[0243] The variation trend of the current efficiency of device 8 with the brightness shows that the brightness of the device is 0.92 cd·m -2 When the current efficiency reaches the maximum value of 62.7cd·A -1 .

[0244] The power efficiency of device 8 is tested with the change of brightness. It can be seen that the device has a brightness of 0.92 cd·m -2 When the power efficiency reaches the maximum value of 77.2lm·W -1 .

[0245] The variation trend of the external quantum efficiency of device 8 with the brightness shows that the device has a brightness of 0.92 cd·m -2 The maximum external quantum efficiency of 19.3% was obtained.

[0246] The electroluminescence spectrum of the test device 8 shows that the electroluminescence peak of the device is at 497 nm.

[0247] The present invention is described in detail above in conjunction with specific embodiments and / or exemplary examples and drawings, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A compound based on a sulfur-phosphorus heterocyclic receptor and a nitrogen-containing heterocyclic donor compound, characterized in that: The sulfur-phosphorus heterocyclic receptor and nitrogen-containing heterocyclic donor compound are:

2. A compound based on a sulfur-phosphorus heterocyclic receptor and a nitrogen-containing heterocyclic donor compound, characterized in that: The sulfur-phosphorus heterocyclic receptor and the nitrogen-containing heterocyclic donor compound are prepared by carbon-nitrogen coupling reaction of a halogenated sulfur-phosphorus heterocyclic compound and a nitrogen-containing heterocyclic compound under the action of a palladium catalyst. The halogenated sulfur-phosphorus heterocyclic compound is: wherein X1 is independently selected from H, Cl, Br or I, preferably selected from H, Cl or Br, more preferably H or Br; X2 is selected from Cl, Br or I, preferably selected from Cl or Br, more preferably Br; The nitrogen-containing heterocyclic compound is phenothiazine.

3. A method for preparing the compound according to claim 1 or 2, characterized in that: In the method, a halogenated sulfur-phosphorus heterocyclic compound and a nitrogen-containing heterocyclic compound are subjected to a carbon-nitrogen coupling reaction in the presence of a palladium catalyst in an alkaline environment to prepare the compound, wherein the nitrogen-containing heterocyclic compound is phenothiazine.

4. The method according to claim 1, characterized in that: The method comprises the following steps: Step 1, preparing a halogenated sulfur-phosphorus heterocyclic compound; Step 2, adding a halogenated sulfur-phosphorus heterocyclic compound, a nitrogen-containing heterocyclic donor compound, a palladium catalyst and an alkaline substance into a reaction solvent, stirring for reaction, and obtaining a reaction solution; Step 3: post-treating the reaction solution to obtain a sulfur-phosphorus heterocyclic receptor and a nitrogen-containing heterocyclic donor compound.

5. The method according to claim 4, characterized in that In step 2, The molar ratio of the halogenated sulfur-phosphorus heterocyclic compound to the nitrogen-containing heterocyclic donor compound is 1:(1.5-7.5), preferably 1:(2.0-7.0), and more preferably 1:(2.5-6.5).

6. The method according to claim 4, characterized in that In step 2, the reaction solvent is selected from one or more of aromatic hydrocarbon solvents, amide solvents and ketone solvents, preferably one or more of toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, cyclohexanone and methyl ethyl ketone.

7. The method according to claim 4, characterized in that In step 2, the palladium catalyst is selected from palladium salts, such as palladium chloride or palladium acetate, palladium carbon, inorganic oxide-supported palladium, such as Pd / Al2O3 or Pd / MgO, palladium complexes, such as Pd(AsPh3)4, di(tri-tert-butylphosphine)palladium, tetrakis(triphenylphosphine)palladium, Pd((MeO)3P)4, preferably palladium salts or palladium complexes, more preferably palladium acetate and / or di(tri-tert-butylphosphine)palladium.

8. A use of a sulfur-phosphorus heterocyclic acceptor and a nitrogen-containing heterocyclic donor compound according to claim 1, characterized in that: It is used as a light-emitting layer material to prepare electroluminescent devices.

9. An electroluminescent device, characterized in that: The light-emitting layer material of the electroluminescent device includes the sulfur-phosphorus heterocyclic acceptor and the nitrogen-containing heterocyclic donor compound; The current efficiency of the electroluminescent device reaches a maximum of 60-70 cd·A at the luminescence peak of 490-500 nm. -1 , the power efficiency reaches a maximum of 70-80lm·W -1 , the maximum external quantum efficiency is 18-25%, and the turn-on voltage is lower than 3V, preferably 2.6V.

10. The device according to claim 9, characterized in that The light-emitting layer material also includes DBFDPO, and the mass fraction of the sulfur-phosphorus heterocyclic acceptor and the nitrogen-containing heterocyclic donor compound in the light-emitting layer material is 10-30%.

Citation Information

Patent Citations

  • Organic electroluminescence material and organic photoelectric device

    CN106831817A

  • Organic electron transport material and organic electroluminescent element using same

    CN108475734A

  • Heterocyclic compound and organic light-emitting device including the same

    CN108794533A

  • Electroluminescent material, electroluminescent material preparation, and light emitting device

    CN109251745A

  • Compound, application thereof and organic light-emitting device comprising compound

    CN111377966A